1999
DOI: 10.1093/pasj/51.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Polarimetry and Color of the Inner Coma of Comet Hale-Bopp(C/1995 O1)

Abstract: Optical-imaging polarimetry of comet Hale-Bopp (C/1995 O1) was performed on 1997 March 17, using the Okayama Optical Polarimetry and Spectroscopy system (OOPS), which was mounted on the 91-cm reflector at Okayama Astrophysical Observatory. Using two different narrow-band filters for the continuum, color maps and polarization maps of dust particles of comet Hale-Bopp were obtained. A dust “jet„ structure (also called ‘arc structure’) was seen in the intensity, polarization, and color maps. The polarization degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…On polarization maps, highly polarized regions correspond to jet-like and arc features (Hadamcik et al 1997;Jockers et al 1997;Jones et al 1997;Furusho et al 1999), as previously observed for 1P/Halley (Eaton et al 1988), C/1990 K1 Levy (Renard et al 1992), C/1996 B2 Hyakutake .…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…On polarization maps, highly polarized regions correspond to jet-like and arc features (Hadamcik et al 1997;Jockers et al 1997;Jones et al 1997;Furusho et al 1999), as previously observed for 1P/Halley (Eaton et al 1988), C/1990 K1 Levy (Renard et al 1992), C/1996 B2 Hyakutake .…”
Section: Introductionsupporting
confidence: 79%
“…The April 1997 polarization maps are in complete agreement with those of Jockers et al (1997) and Furusho et al (1999) in the visible domain. The polarization in the arcs decreases when the dust moves away from the nucleus.…”
Section: Comparison With Other Polarization Maps Of Comet Hale-boppsupporting
confidence: 68%
See 1 more Smart Citation
“…This might cause some change in the degree of polarization provided the sampled region is heterogeneous. The inner coma region of comets has been found to be quite heterogeneous in the spatial distribution of dust, which in turn is responsible for the spatial variation of polarization in the inner region Eaton et al 1988Eaton et al , 1991Dollfus & Suchail 1987;Jockers et al 1999;Furusho et al 1999;Kolokolova et al 2001). In the case of Comet Halley a fair degree of agreement is seen among the observations made by different groups with different aperture sizes as long as the polarization is estimated over the whole coma with a large aperture centered on the nucleus which averages out the effect of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…3. As the colour of the grains do not change drastically with phase angle, we set a conservative limit of 5−10% per 1000Å on the shells and 10−20% per 1000Å on the regions between the shells representing the coma based on the colour reported by Bellucci (1998), Furusho et al (1999), Kiselev & Velichko (1997) and Kolokolova et al (2001). 4.…”
Section: Observational Inputsmentioning
confidence: 99%